2017
DOI: 10.7906/indecs.15.4.1
|View full text |Cite
|
Sign up to set email alerts
|

The Embodiment of Power and Visual Dominance Behaviour

Abstract: The objective of this study was to identify whether the changes in assuming power poses during a conversation between a pair of individuals, who were previously familiar with each other, influence the hierarchy of power, changes in it, as well as maintenance and adoption of different roles in the hierarchy. We assumed changes in roles of power on the basis of changes in visual dominance behaviour, which proved to be a reliable indicator of the social power of the individual in previous researches. Each pair co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Moreover, very few power posing studies have so far used designs that allow attributing the change to the expansive or contracted poses by including a neutral condition. Within-subject studies observed either a change only after expansive poses [91,92] or no significant effect [33]. Similarly, only a few studies included a control group, and observed a significant difference only for the contracted pose [36] or no significant effects [21,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, very few power posing studies have so far used designs that allow attributing the change to the expansive or contracted poses by including a neutral condition. Within-subject studies observed either a change only after expansive poses [91,92] or no significant effect [33]. Similarly, only a few studies included a control group, and observed a significant difference only for the contracted pose [36] or no significant effects [21,26].…”
Section: Discussionmentioning
confidence: 99%
“…By demonstrating pose effects on elementary social behavior with reasonable statistical power, the present study makes a valuable contribution to the literature. Most importantly, it is the first larger study investigating elementary social behavior, with the only earlier study having a very small sample (n = 22 [33]). Although power poses are primarily a social signal of dominance in many animal species, most previous studies have focused on non-social behavior or high-level cognitive processes, such as risky gambling, abstract thinking, or sales negotiations [20,90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation